2017
DOI: 10.1080/01639625.2017.1411030
|View full text |Cite
|
Sign up to set email alerts
|

Offending and Victimization in the Digital Age: Comparing Correlates of Cybercrime and Traditional Offending-Only, Victimization-Only and the Victimization-Offending Overlap

Abstract: Cybercrime research suggests that, analogous to traditional crime, victims are more likely to be offenders. This overlap could be caused by shared risk factors, but it is unclear if these are comparable to traditional risk factors. Utilizing a high risk sample of computer-dependent cyber-offenders and traditional offenders (N = 535) we compare victimization, offending, and victimization-offending between cybercrime and traditional crime. Cybercrime results show a considerable victim-offender overlap and correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…They do not specifically look for them in specific IT-systems. Similarly, both traditional criminal opportunities as well as cybercriminal opportunities generally arise during normal daily activities (Weulen Kranenbarg et al 2017, 2018.…”
Section: Rational Choice Theorymentioning
confidence: 99%
“…They do not specifically look for them in specific IT-systems. Similarly, both traditional criminal opportunities as well as cybercriminal opportunities generally arise during normal daily activities (Weulen Kranenbarg et al 2017, 2018.…”
Section: Rational Choice Theorymentioning
confidence: 99%
“…It is important to control for low self-control because it could potentially influence both the likelihood of offending and the likelihood of selecting deviant friends or being influenced by deviant friends, as argued by Gottfredson and Hirschi (1990). Furthermore, analogous to traditional crime, studies have shown that low self-control is a predictor of cyber-dependent offending, even when social learning measures are included (for example, Bossler and Burruss, 2011;Donner et al, 2014;Holt et al, 2012a;Hu et al, 2013;Marcum et al, 2014;Weulen Kranenbarg et al, 2017a). Therefore, it is important to measure to what extent low self-control is related to having cyber-dependent deviant social ties.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has found a link between IT skills and cyber-dependent offending (Holt et al, 2012a;Morris and Blackburn, 2009;Weulen Kranenbarg et al, 2017a) and some research has claimed that the IT skills necessary to commit cyber-dependent crimes could be learned from deviant friends by imitation (for example, Holt et al, 2012a;Holt et al, 2010;Morris and Blackburn, 2009). Therefore, we included ego's IT skills in our analyses as well, to see to what extent having a cyber-dependent deviant alter is related to IT skills.…”
Section: Methodsmentioning
confidence: 99%
“…Self-reported computer skills was measured with the following item: “When I compare my current computer skill level with that of my peers, I consider my skills to be: (0) Far below average”; (1) Below average; (2) Average; (3) Above average; or (4) Far above average.” Levels of computer skills may be related to digital piracy (Gunter, 2009) and more advanced forms of hacking (Kranenbarg et al, 2019; Morris & Blackburn, 2009), but not minor forms of hacking in college samples (Berenblum et al, 2019).…”
Section: The Present Studymentioning
confidence: 99%